Determination of the major axis direction and macroseismic epicenter of the assessed intensity map based on relocated aftershock sequences - Xu, Zhishuang; Liu, Jie; Yalikun, Alimujiang; Li, Xiaoli; Ren, Jing; Wen, Xintao (Frontiers in Earth Science, 2023)
The rapid assessment of an intensity map following a strong earthquake forms the foundation for risk assessment and emergency response in Chinese mainland. The determination of the major axis direction in the assessed intensity map depends on various factors, including nearby active faults, instrumental intensities, and the distribution of aftershocks. To evaluate the effectiveness of promptly determining the major axis direction based on early aftershock distribution, we relocated and analyzed aftershock sequences occurring within 2 h of eighteen aftershock-rich earthquakes with a magnitude of Ms≥f nitin Chinese mainland from 2012 to 2021. HypoDD was used for relocation, and the standard deviational ellipse fitting technique was employed for analysis. Comparing the aftershock ellipses resulting from our analysis with the macroseismic intensity maps obtained from field surveys reveals a high level of agreement, with an average difference of approximately 9° in the major axis directions of the aftershock ellipses and the meizoseismal zones. For the majority of earthquakes, regardless of focal mechanisms, the lengths of the major axes of the aftershock ellipses closely correspond to the intensity VIII scale. Additionally, the spatial distribution of aftershocks aids in distinguishing the seismogenic fault from the two fault planes with distinctly different dips as indicated by the focal mechanism solution. Moreover, the distance between the aftershock center and the macroseismic epicenter systematically increases as the dip decreases. These findings hold significant scientific value as they contribute to the prompt determination of assessed intensity maps and provide effective guidance for earthquake emergency response.